Enthalpies of Combustion and Formation of Severely Crowded Methyl-Substituted 1,3-dioxanes. The Magnitudes of 2,4-and 4,6-diaxial Me,Me-Interactions and the Chair-2,5-twist Energy Difference - Pihlaja K; Kivelä H; Vainiotalo P; Steele WV (MDPI, 2025)
Enthalpies of combustion of 2,2-trans-4,6- (1) and 4,4,6,6-tetramethyl- (2) and 2,4,4,6,6- (3) and 2,2,4,4,6-pentamethyl-1,3-dioxanes (4) were determined to estimate their enthalpies of formation in the gas phase. By comparing the latter with the corresponding enthalpies estimated based on the various bond-bond interactions allowed to determine the chair-2,5-twist energy difference (Delta H-CT= 29.8 kJ mol(-1)) for 1 since C-13 shift correlations indicate that it escapes to the 2,5-twist form where the 2-methyl groups are isoclinal and 4- and 6-methyl groups pseudoequatorial to avoid syn-axial interactions. Compounds 2 and 3 in turn give the values 21.0 and 21.6 kJ mol(-1)for the 4,6-diaxial Me,Me-interaction. Finally compound 4, which retains the chair conformation to avoid pseudoaxial interactions in the twist forms gives the value 19.5 kJ mol(-1)for the 2,4-diaxial Me,Me-interaction indicating that its chair form appears to be somewhat deformed.